2016
DOI: 10.1155/2016/9213623
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Altered Platelet Morphological Parameters and Retinopathy in Patients with Type 2 Diabetes Mellitus

Abstract: Purpose. To investigate whether platelet morphology or function is altered in patients with diabetic retinopathy (DR). Methods. This prospective study enrolled 85 healthy controls (HCs) (group 1) and 262 patients with Type 2 diabetes mellitus (T2DM). Patients were subclassified into three groups according to ocular findings: no DR (group 2; n = 88); nonproliferative DR (group 3; n = 88), and proliferative DR (group 4; n = 86). Mean platelet volume (MPV), platelet distribution width (PDW), platelet large cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
5
17
0
Order By: Relevance
“…The number of the included subjects in the case group and the control group ranged from 20 to 328 and 20 to 192, respectively. Of these 48 articles, 27 came from China [ 22 , 30 , 34 , 36 , 37 , 41 , 43–46 , 48 , 49 , 55–60 , 64 , 65 , 67 , 68 , 70–73 ], 16 from Turkey [ 21 , 23 , 29 , 31 , 35 , 38 , 40 , 42 , 47 , 50–54 , 61 , 69 ], 3 from India [ 32 , 63 , 39 ], 1 from Greece [ 62 ] and 1 from Kazakhstan [ 33 ]. Amongst these studies, 21 reported NLR (9 enrolled patients with DR, 12 enrolled patients with DN) [ 21 , 23 , 31 , 32 , 34 , 35 , 38 , 41–43 , 45 , 47 , 50–54 , 56–60 , 62 , 63 , 65 , 67–69 , 71–73 ], 33 reported the data of MPV (23 enrolled patients with DR, 10 enrolled patients with DN) [ 22 , 29 , 30 , 33 , 36–40 , 44 , 46 , 48–50 , 55 , 61 , 64 , 66 , 70 , 73 ], and 12 reported PDW (12 enrolled patients with DR, 3 enrolled patients with DN) […”
Section: Resultsmentioning
confidence: 99%
“…The number of the included subjects in the case group and the control group ranged from 20 to 328 and 20 to 192, respectively. Of these 48 articles, 27 came from China [ 22 , 30 , 34 , 36 , 37 , 41 , 43–46 , 48 , 49 , 55–60 , 64 , 65 , 67 , 68 , 70–73 ], 16 from Turkey [ 21 , 23 , 29 , 31 , 35 , 38 , 40 , 42 , 47 , 50–54 , 61 , 69 ], 3 from India [ 32 , 63 , 39 ], 1 from Greece [ 62 ] and 1 from Kazakhstan [ 33 ]. Amongst these studies, 21 reported NLR (9 enrolled patients with DR, 12 enrolled patients with DN) [ 21 , 23 , 31 , 32 , 34 , 35 , 38 , 41–43 , 45 , 47 , 50–54 , 56–60 , 62 , 63 , 65 , 67–69 , 71–73 ], 33 reported the data of MPV (23 enrolled patients with DR, 10 enrolled patients with DN) [ 22 , 29 , 30 , 33 , 36–40 , 44 , 46 , 48–50 , 55 , 61 , 64 , 66 , 70 , 73 ], and 12 reported PDW (12 enrolled patients with DR, 3 enrolled patients with DN) […”
Section: Resultsmentioning
confidence: 99%
“…31 Yilmaz et al, had found that Mean platelet volume is correlating directly with the stage of diabetic retinopathy. 32 Mean platelet volume is also correlating with diabetic retinopathy, nephropathy and HbA1C levels. 29,33 Mean platelet volume was also found to be related positively with the microalbuminuria and diabetic nephropathy.…”
Section: Mean Platelet Volumementioning
confidence: 99%
“…Some authors suggest that larger platelets are metabolically more active than smaller platelets, that they have faster rates of aggregation and release higher quantities of pro-thrombotic elements such as TxA 2 and ADP [97]. MPV and PDW levels can be altered in several diseases including T2DM [98], CVD and atherosclerosis [93] (Berger et al, 2010), and in this regard they have been suggested as markers of subclinical platelet activation. PLCR and PCT may serve as sensitive biomarkers of platelet health [99].…”
Section: Platelet Indicesmentioning
confidence: 99%